Xylose and Glucose Utilization by Bacteroides xylanolyticus X5-1 Cells Grown in Batch and Continuous Culture - Biesterveld, Steef (1994)
During cultivation on a mixture of xylose and glucose, Bacteroides xylanolyticus X5-1 showed neither diauxic growth nor a substrate preference. Xylose-limited continuous-culture cells were able to consume xylose and glucose both as single substrates and as mixed substrates without any lag phase. When glucose was the growth-limiting substrate, the microorganism was unable to consume xylose. However, in the presence of a small amount of glucose or pyruvate, xylose was utilized after a short lag phase. In glucose-limited cells, xylose isomerase was present at low activity but xylulose kinase activity could not be detected. On addition of a mixture of xylose and glucose, xylose isomerase was induced immediately and xylulose kinase was induced after about 30 min. The induction of the two enzymes was sensitive to chloramphenicol, showing de novo synthesis. Xylose uptake in glucose-grown cells was very low, but the uptake rate could be increased when incubated with a xylose-glucose mixture. The increase in the uptake rate was not affected by chloramphenicol, indicating that a constitutive uptake system had to be activated. The inability of B. xylanolyticus X5-1 cells undergoing glucose-limited continuous culture to induce the xylose catabolic pathway after the addition of only xylose probably was caused by energy limitation.